2021
DOI: 10.3389/fonc.2020.595734
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Care of Children, Adolescents and Adults With Autism Spectrum Disorders: Key Information and Strategies for Oncology Teams

Abstract: Delivering optimal cancer care to children, adolescents and adults with ASD has recently become a healthcare priority and represents a major challenge for all providers involved. In this review, and after consideration of the available evidence, we concisely deliver key information on this heterogenous group of neurodevelopmental disorders, as well as recommendations and concrete tools for the enhanced oncological care of this vulnerable population of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…In the absence of higher-grade evidence, they are intended as a call for vigilance of the particularities of these highly vulnerable individuals. (Vuattoux et al, 2021). In one study exploration of the mutations, reconstructed disorder specific networks, pathways, and transcriptome levels and profiles of autism spectrum disorder (ASD) and cancers, point to signalling strength as the key factor: strong signalling promotes cell proliferation in cancer, and weaker (moderate) signalling impacts differentiation in ASD (Yavuz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of higher-grade evidence, they are intended as a call for vigilance of the particularities of these highly vulnerable individuals. (Vuattoux et al, 2021). In one study exploration of the mutations, reconstructed disorder specific networks, pathways, and transcriptome levels and profiles of autism spectrum disorder (ASD) and cancers, point to signalling strength as the key factor: strong signalling promotes cell proliferation in cancer, and weaker (moderate) signalling impacts differentiation in ASD (Yavuz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…12 Other studies have not suggested an increased association. 13,14 The prevalence of autism in a North Carolina population found that out of 702 cancer patients, seven (1%, 95% CI of 0.4% -2.04%) were labeled as AD in their medical records. The diagnosis of AD was made prior to cancer presentation in five of the seven of the patients; in the other two, obvious behavioral issues at cancer presentation led to an evaluation which suggested AD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other studies have not suggested an increased association. 11,12 The prevalence of autism in a North Carolina population found that out of 702 cancer patients, seven (1%, CI of 0.4%-2.04%) were labeled as AD. The diagnosis of AD was made prior to cancer presentation in five of the seven patients; in the other two, behavioral issues at cancer presentation led to an evaluation that suggested AD.…”
Section: E T T E R T O T H E E D I T O R B-cell Lymphoblastic Leukemi...mentioning
confidence: 99%
“…/46, XX, inv(9)(p12q13)c[12]. She received anti-leukemic therapy per Children's Oncology Group (COG) AALL1732 and is currently in complete remission.She had first demonstrated seizures at age of 4 months 2−3 days after her immunizations, which consisted of staring and lasted for as long as 1 minute.…”
mentioning
confidence: 99%